A ACESC e a humanização do mercado da morte em Cascavel – PR. - Machado, Marilana Aparecida (2018)
This dissertation discusses about the death market in Cascavel city, Paraná. The research was carried out at ACESC - Administration of Cemeteries and Funeral Services of Cascavel - a municipal autarchy, founded in 1989, whose main purpose is managing the funeral system of the municipality. It aims at verifying, throughout this study, if the philosophy of death humanization, which is proposed as an innovative decision-making according to the funeral market model that already existed at the foundation period, keeps on being applied in the service rendered to the bereaved relatives and the deceased one. The research was carried out in this institution and developed based on ethnography. It was observed the completely postmortem process, which begins on the mourners’ care and ends at the burial. Its main goal was to analyze the death market with emphasis on the consumption of articles and services used at funerals. Thus, interviews, bibliographical and documentary reviews were carried out based on fieldwork. Therefore, it was possible to understand that the death market managed by ACESC is based on its founding principles, even though it has recently been possible to observe that private companies have an opportunity to take part in the supply of items used in the rites of death currently practiced.